First-Principles Study on the Nanofriction Properties of Diamane: The Thinnest Diamond Film - Jianjun Wang; Lin Li; Jiudong Wang; Wentao Yang; Peng Guo; Meng Li; Dandan Liu; Haoxian Zeng; Bin Zhao (Nanomaterials, 2022)
Diamane, the thinnest sp3-hybridized diamond film, has attracted great interest due to its excellent mechanical, electronic, and thermal properties inherited from both graphene and diamond. In this study, the friction properties of surface hydrogenated and fluorinated diamane (H- and F-diamane) are investigated with dispersion-corrected density functional theory (DFT) calculations for the first time. Our calculations show that the F-diamane exhibits approximately equal friction to graphene, despite the presence of morphological corrugation induced by sp3 hybridization. Comparative studies have found that the coefficient of friction of H-diamane is about twice that of F-diamane, although they have the same surface geometric folds. These results are attributed to the packed charge surface of F-diamane, which can not only effectively shield carbon interactions from two contacting films, but also provide strong electron–electron repulsive interaction, resulting in a large interlayer distance and a small wrinkle of potential energy at the interface. The interesting results obtained in this study have enriched our understanding of the tribological properties of diamane, and are the tribological basis for the design and application of diamane in nanodevices.